Mitophylogenetic patterns in Tettigoniidae: Insights from the complete mitogenome of Saga natoliae (Orthoptera) - Karakaş, Müşerref Y.; Uluar, Onur; Yartaş, Mustafa; Çiplak, Battal (Zootaxa, 2025)
Although there is a consensus on the distinctiveness of Saginae, its phylogenetic position within Tettigoniidae remains a topic to debate. Comprehensive DNA data are essential for clarifying subfamilial relationships within the Tettigoniidae. This study investigates the complete mitogenome of Saga natoliae, providing critical insights into the phylogenetic position of the Saginae. To achieve this, we established two datasets: the first comprises total mitogenome sequences from all published representatives of Tettigoniidae subfamilies and tribes, while the second includes partial mitogenome sequences from subfamilies not represented in the first dataset. The first dataset produced a well-resolved phylogenetic tree, whereas the second exhibited limited resolution. By synthesizing results from both the following conclusions were made: (1) The mitogenome of Saga natoliae displays typical characteristics of both Pancrustaceae and Orthoptera. (2) The mitophylogeny of Tettigoniidae reveals four main clades: (i) Saginae, (ii) Lipotactinae, (iii) the Tettigonioid clade (including Tettigoniidae + Bradyporinae, Hexacentrinae, Conocephalinae, and Meconematinae) and (iv) the Phaneropteroid clade (comprising Pseudophyllinae, Mecopodinae, and Phaneropterinae). Consequently, Saginae is established as a distinct internal lineage, referred to as the Saginoid clade. (3) Our findings do not support close relationships between Saginae and Zaprochilinae, Tympanophorinae and Phasmodinae. (4) Data confirm that Saginae is a monophyletic subfamily, likely originated in Africa and subsequently dispersed to the West Palearctic region.